Comparison of Maceration and Ultrasound-Assisted Extraction Method in Determining Quercetin Content of Clitoria ternatea L. Flowers - Wardatun, Sri; Ahyar, Akmal Zainul; Nining, Euis (Universitas Pakuan, 2024)
Butterfly pea flowers (Clitoria ternatea L.) contain the compound quercetin which has been studied extensively. Butterfly pea flowers have shown various pharmacological activities. The extraction method has an impact on the amount of active compound extracted. The aim of this research was to determine the effect of different extraction methods on quercetin content of C. ternatea L flowers using the High-Performance Liquid Chromatography (HPLC). The HPLC system uses an ODS-3 column stationary phase; a mobile phase mixture of 0.1 % orthophosphoric acid and methanol (36:64); a flow rate of 1.2 mL/min; and a PDA-UV detector. The extraction methods used were maceration, and ultrasound-assisted extraction (UAE) using methanol as a solvent. The results showed that the quercetin content of C. ternatea L flower extract with maceration method results was 1.0669 ± 0.0283 mg/g and with UAE method was 1.3915 ± 0.1789 mg/g. Statistical test results showed that differences in both extraction method did not have a significant effect on quercetin content. However, the UAE method is considered more efficient in terms of extraction time, so the UAE method can be used as an alternative for extracting quercetin from C. ternatea L. flowers.